PENGARUH TINGKAT PENERAPAN PELATIHAN, DISIPLIN PREVENTIF DAN SISTEM PEMBERIAN TUNJANGAN TERHADAP KINERJA KARYAWAN PADA PT. LINGGA PERDANA CILEGON - Herlina Juniyanti; Vera Maria (Bajang Institute, 2022)
The Influence of Training Application Level, Preventive Discipline, System of Providing Allowances on Employee Performance (Case Study at PT. Lingga AbstractPerdana Kota Cilegon) is the thesis title of Herlina Juniyanti (5551170119), a student of Sultan Ageng Tirtayasa University Faculty of Economics and Business, Department of Management (Resource Management Human) under the guidance of Vera Maria, SE., MM as mentor I and Sri Ndaru Arthawati, MM as mentor II. This study aims to determine the effect of the Training Application Level (X1) of Preventive Discipline (X2) and the System of Providing Allowances (X3) on Employee Performance (Y) at PT. Lingga Perdana City of Cilegon. In this research, the type of research used is quantitative with a descriptive approach, the population in this study are employees at PT. Lingga Perdana Kota Cilegon, with a total of 150 employees. The sample in this study amounted to 60 respondents who were determined by the Slovin formula. The research instrument trial was conducted at PT. Lingga Perdana Kota Cilegon with sampling using probability sampling method, and in measuring the questionnaire using the Likert scale, the data analysis methods used were data quality test, classical assumption test and multiple linear test with the help of IBM SPSS version 25 software.